Remoção de oocistos de Cryptosporidium parvum E de indicadores no tratamento de água por ciclo completo, filtração direta descendente e dupla filtração, em escala piloto - Daniel Adolpho Cerqueira (2008)
Removal of oocysts in drinking water has on granular bed filtration, with previous coagulation and with or without sedimentation an efficient barrier for Cryptosporidium control. USA regulation for Cryptosporidium control in drinking water awards 3,0 log removal to conventional treatment and 2,5 log to direct filtration. In this pilot scale study, conventional treatment, double and direct downflow filtration were evaluated on theirefficiency on oocysts, microspheres and Bacillus subtilis spore removal. Conventional treatment and double filtration were submitted to 100 ± 5,0 uT water turbidity and double and direct downflow filtration to 10 ± 0,5 uT water turbidity, both synthetically prepared with well water and caolim solution. The three processes, regardless the initial turbidity water,presented similar efficiency on oocysts removal, with a median of about 2,7 log removal rate. Turbidity was better removed by double filtration, compared to conventional treatment and direct downflow filtration. Higher oocyst removal was not observed, for all evaluated technology, when filtration effluent samples presented turbidity under 0,5 or o,3 uT. Oocyst,turbidity and microsphere removal profiles were similar and microspheres were correlated with the other parameters in all the process and turbidity condition evaluated. Oocyst removal rate in double filtration under the lower affluent turbidity had shown good correlation withremoval of turbidity. Aerobic spores presented the worst removal rate amongst the parameters, under the three processes and presented good correlation with microspheres under the direct downflow filtration. Since double filtration presented oocyst removal efficiency similar to conventional and direct downflow filtration technologies and due to its relatively low building cost, it could be better evaluated as a promising treatment technology and a significant barrier for at Cryptosporidium removal.